The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00405-011-1542-x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal packing and transseptal suturing techniques: surgical and anaesthetic perspectives

Abstract: The objective of this study is to compare the nasal packing and the transseptal suturing techniques regarding the extubation difficulty evaluation scores, follow-up times in post-anaesthesia care unit (PACU), pain scores, and postoperative complications. Two hundred patients who underwent septoplasty from January 2009 to October 2009 were randomly assigned either to have nasal packs (n: 100) or transeptal sutures (n: 100). In the transseptal suture group, extubation was easier and PACU follow-up times were sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 15 publications
5
50
0
2
Order By: Relevance
“…Even for septoplasty procedures, the evidence suggests that packing is not only unnecessary but can lead to discomfort, pain, and anxiety, thereby diminishing patient satisfaction. 116 More severe potential risks include toxic shock syndrome, 108,109 pack-related sleep apnea, 117 and challenges with postoperative CPAP delivery.…”
Section: Supporting Textmentioning
confidence: 99%
“…Even for septoplasty procedures, the evidence suggests that packing is not only unnecessary but can lead to discomfort, pain, and anxiety, thereby diminishing patient satisfaction. 116 More severe potential risks include toxic shock syndrome, 108,109 pack-related sleep apnea, 117 and challenges with postoperative CPAP delivery.…”
Section: Supporting Textmentioning
confidence: 99%
“…4 There is a distinction between the normal flora of the nasal vestibule and those of the nasal cavity concerning potential infectious pathogens (PIPs), in particular, Staphylococcus aureus. 5,6 So far, only a few microbiological studies have been undertaken to differentiate the micro-organisms of the vestibule and cavity, although divergent bacterial colonization can be anticipated because Background and objective: Septoplasty is one of the most common procedures worldwide in otolaryngology clinics. The use of antibiotics in Septoplasty is a common practice among most otolaryngologists.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] Nasal packing may lead to complications such as mucosal injury, loss of ciliary function, worsening of breathing due to sleep disorders, displacement and aspiration of the packing material, allergy, toxic shock syndrome, postoperative infections and eustachian tube dysfunction. [1,3,4] In addition, nasal pack application following nasal surgery requires hospitalization until the pack is removed and causes more pain compared to that caused by surgery postoperatively and during the process of pack removal.…”
mentioning
confidence: 99%
“…[4] Therefore, nasal packing--commonly used after septoplasty and inferior turbinate surgeries and even considered one of the basic steps of surgery--has increasingly been replaced by the use of nasal splints and suture techniques. Clinical studies have demonstrated that nasal septal splints and trans-septal suturing after septoplasty caused less postoperative pain but similar results in the prevention of postoperative complications compared to packing.…”
mentioning
confidence: 99%
See 1 more Smart Citation